Digital Marketing Standardization Strategy for Photoism Using K-pop Artists via Instagram for 2022-2024 (Wahana : Tridarma Perguruan Tinggi, 2025)
Photo booth is a self-photo service with a series of components designed to capture photos automatically using digital cameras equipped with technology such as computers and printers to control and print the photos. Photoism, one of the multinational companies engaged in photography, is the largest self-help studio in South Korea that provides photo booth services. Photoism's success in marketing its photography services cannot be separated from the influence of the popularity of Korean culture (Hallyu Wave) which is widely favored by the younger generation. Through its collaboration with several Kpop agencies, Photoism has successfully expanded to various countries with a total of more than 220 branches. This research will focus on the digital marketing standardization strategy of Photoism using Kpop Artist through Instagram social media in 2022-2024. The research is conducted using a qualitative descriptive method with secondary data collection techniques through literature studies. The resarch showed how Photoism's digital marketing standardization strategy through social media for the service products offered in collaboration with K-pop idols to create aligned standards across all branch locations. The research results show a standardized form of Photoism marketing through its official Instagram in various countries as a strategy to expand market reach and enhance Photoism branding in the international arena.